Intention‐to‐treat analyses and missing outcome data: A tutorial - Chaplin, Marty; Dwan, Kerry (Cochrane evidence synthesis and methods, 2024)
This tutorial focuses on “intention‐to‐treat” analyses and missing outcome data in systematic reviews. There is a lack of consensus on the definition of the ITT approach. We will explain the principles of an intention‐to‐treat analysis, and outline the key issues you need to consider when planning, conducting and writing up your systematic review. ITT micro learning module